2009
DOI: 10.1155/2009/827405
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Infectious Morbidities of Cesarean Delivery in Human Immunodeficiency Virus-Infected Women

Abstract: Objective. To compare the infectious complication rates from cesarean delivery of human immunodeficiency virus (HIV)-infected women and HIV-negative women. Materials and Methods. A retrospective analysis was performed on data derived from HIV-infected women and HIV-negative women, who underwent cesarean delivery at two teaching hospitals. Main outcome measures were infectious postoperative morbidity. Descriptive, comparison analysis, and multiple logistic regression analysis were performed. Results. One hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Based on previous studies of mode of delivery and maternal morbidity, maternal disease severity measures including last CD4 count, viral load, CDC classification during pregnancy, and clinical diagnoses during pregnancy were forced in all final multiple regression models to adjust for potential confounding by indication. 46, 9, 10 Odds ratios and 95% confidence intervals were obtained from the final regression models as estimates of the adjusted association between mode of delivery and each maternal morbidity outcome. Statistical significance was defined as two-sided p-value < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies of mode of delivery and maternal morbidity, maternal disease severity measures including last CD4 count, viral load, CDC classification during pregnancy, and clinical diagnoses during pregnancy were forced in all final multiple regression models to adjust for potential confounding by indication. 46, 9, 10 Odds ratios and 95% confidence intervals were obtained from the final regression models as estimates of the adjusted association between mode of delivery and each maternal morbidity outcome. Statistical significance was defined as two-sided p-value < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…5 A later study from New Orleans suggested morbidity in HIV infected women undergoing cesarean was due to other co-morbidities aside from HIV. 9 Likewise, data from a Latin American HIV infected pregnant cohort suggested low rates of morbidity. 7 European data also reports conflicting results regarding morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was not found higher frequency of puerperal infection in pregnant women infected with HIV (23,24) . Few studies report higher incidence of birth of female fetuses (25,26) , which constitutes a peculiar finding of the present study, maybe relevant because there are more reports of TV for female fetuses (27) .…”
Section: Discussionmentioning
confidence: 75%
“…More recent cohort data from Europe and from case controlled studies in the USA and the UK involving women on cART with undetectable viral loads have demonstrated very low rates of maternal morbidity, irrespective of mode of delivery.…”
Section: Obstetric Managementmentioning
confidence: 99%